2003
DOI: 10.1523/jneurosci.23-10-04117.2003
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of Extracellular Signal-Regulated Protein Kinase in Primary Afferent Neurons Regulates Brain-Derived Neurotrophic Factor Expression after Peripheral Inflammation and Nerve Injury

Abstract: To investigate the intracellular signal transduction pathways involved in regulating the gene expression of brain-derived neurotrophic factor (BDNF) in primary afferent neurons, we examined the activation of extracellular signal-regulated protein kinase (ERK) in dorsal root ganglion (DRG) neurons after peripheral inflammation and sciatic nerve transection. Peripheral inflammation induced an increase in the phosphorylation of ERK, mainly in tyrosine kinase A-containing small-to-medium-diameter DRG neurons. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
186
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(200 citation statements)
references
References 78 publications
(82 reference statements)
13
186
0
1
Order By: Relevance
“…In the ipsilateral L5 DRG, the L5 SNL induced an increase in the phosphorylation of ERK, mainly in large DRG neurons and in satellite glial cells (Fig. 2 A, B), consistent with a previous study (Obata et al, 2003b). Seven days after L5 SNL surgery, 46 of 313 p-ERK-IR neurons counted (14.7%) were small, 76 (24.3%) were medium, and 191 (61.0%) were large in size (mean Ϯ SD of the cross-sectional area, 1414 Ϯ 673 m 2 ) (Fig.…”
Section: L5 Snl Induces Differential Activation Of Mapk In Injured L5supporting
confidence: 92%
See 2 more Smart Citations
“…In the ipsilateral L5 DRG, the L5 SNL induced an increase in the phosphorylation of ERK, mainly in large DRG neurons and in satellite glial cells (Fig. 2 A, B), consistent with a previous study (Obata et al, 2003b). Seven days after L5 SNL surgery, 46 of 313 p-ERK-IR neurons counted (14.7%) were small, 76 (24.3%) were medium, and 191 (61.0%) were large in size (mean Ϯ SD of the cross-sectional area, 1414 Ϯ 673 m 2 ) (Fig.…”
Section: L5 Snl Induces Differential Activation Of Mapk In Injured L5supporting
confidence: 92%
“…The intrathecal delivery of MAPK inhibitors or anti-NGF was performed basically as described previously Obata et al, 2003b). A laminectomy of the L5 vertebra was performed under adequate anesthesia with sodium pentobarbital.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ERK (extracellular signal-regulated kinase) members of the MAPK family are originally identified as the primary effectors of growth factor receptor signaling [200] and supposed to regulate a wide array of cellular functions, including cell growth, differentiation, survival, as well as neuronal plasticity [201][202][203] . Nowadays, a growing number of reports also indicate that activated forms of ERKs would act both in the peripheral nociceptor terminal and the dorsal horn to produce pain hypersensitivity and hence contribute to the pathology of inflammatory and neuropathic pain [204][205][206][207][208] .…”
Section: Egr1 Expression the Zinc Finger Transcription Factormentioning
confidence: 99%
“…Indeed, a number of putative inflammatory mediators, including cytokines and NGF, can activate the Ras/MEK/ERK signaling pathway in sensory neurons (Hensellek et al 2007;Nicol and Vasko 2007;Zhuang et al 2004), and the consequences of long-term activation of this pathway are the subject of much study. Several investigations have shown that phosphorylation and activation of ERK are involved in peripheral sensitization (Dai et al 2002;Ji et al 1999;Obata et al 2003;Zhuang et al 2004). Furthermore, there is evidence that activation of the Ras/Raf/MEK/ERK pathway mediates neurotrophin-induced increases in expression of transient receptor potential cation channel subfamily V member 1 (TRPV1) (Bron et al 2003).…”
mentioning
confidence: 99%